Reflections on the assessment of graphic design teaching in the university - García Pacheco, Nancy Patricia (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The article aims at reflecting on the assessment practice. Therefore, it deals with an experience with students of the University of Boyaca Graphic Design program, in which their perception on assessment is explored. It is paramount to think of an assessment culture aiming at a true quality education articulated to innovation in pedagogical practices. It is of first importance to leave aside those measurements that do not account for cognitive processes developed by every person on the basis of his/her own learning experience. This research found out that in the case of Graphic Design, assessment is subjective, since teachers are given all the power to argue from their own interpretation of a visual reality which may differ from the perception and meaning every person gives to it. Then, positions by some teachers of the program about this topic are presented. Finally, the article states some conclusions arising from that reflection.